Genetic architecture behind developmental and seasonal control of tree growth and wood properties in Norway spruce - Chen, Zhi-Qiang; Zan, Yanjun; Zhou, Linghua; Karlsson, Bo; Tuominen, Hannele; García-Gil, Maria Rosario; Wu, Harry X. (Frontiers in Plant Science, 2022)
Genetic control of tree growth and wood formation varies depending on the age of the tree and the time of the year. Single-locus, multi-locus, and multitrait genome-wide association studies (GWAS) were conducted on 34 growth and wood property traits in 1303 Norway spruce individuals using exome capture to cover 130K single nucleotide polymorphisms (SNPs). GWAS identified associations to the different wood traits in a total of 85 gene models, and several of these were validated in a population of the mother trees. A multi-locus GWAS model identified more SNPs associated with the studied traits than single-locus or multivariate models. Changes in tree age and annual season influenced the genetic architecture of growth and wood properties in unique ways, manifested by non-overlapping SNP loci. In addition to completely novel candidate genes, SNPs were located in genes previously associated with wood formation, such as cellulose synthases and a NAC transcription factor, but that have not been earlier linked to seasonal or age-dependent regulation of wood properties. Interestingly, SNPs associated with the width of the year rings were identified in homologs of Arabidopsis thaliana BARELY ANY MERISTEM 1 and rice BIG GRAIN 1 which have been previously shown to control cell division and biomass production. The results provide tools for future Norway spruce breeding and functional studies.